Maternal mental health : a prospective longitudinal cohort study of the outcome of planned versus unplanned pregnancy in women with major psychiatric disorders in a developing country - Du Toit, Elizabeth (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.